2015
DOI: 10.1161/circresaha.115.306319
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Hypoxia-Regulated Endothelial Circular RNA

Abstract: Rationale: Circular RNAs (circRNAs) are noncoding RNAs generated by back splicing. Back splicing has been considered a rare event, but recent studies suggest that circRNAs are widely expressed. However, the expression, regulation, and function of circRNAs in vascular cells is still unknown. Objective: Here, we characterize the expression, regulation, and function of circRNAs in endothelial cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
254
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 312 publications
(267 citation statements)
references
References 19 publications
10
254
2
Order By: Relevance
“…Additional avenues for future investigation could include querying the cardiac Ago2 HITS-CLIP data for other biologically-relevant miR binding sites within coding regions, particularly those which may elicit splice-isoform specific gene suppression. This data resource may also guide future interrogations of intriguing Ago2 bindings sites within intronic regions, long non-coding RNAs (lncRNAs) and perhaps even circular RNAs (circRNAs) (46), as the functional relevance of these sites remains largely unknown. Although our luciferase data mostly point to gene suppression mechanisms for the tested miR binding sites, these experiments need to be followed-up in more biologically-relevant contexts, keeping in mind that some interactions may function as miR ‘sponges’ in competing endogenous RNA (ceRNA) expression networks (47).…”
Section: Discussionmentioning
confidence: 99%
“…Additional avenues for future investigation could include querying the cardiac Ago2 HITS-CLIP data for other biologically-relevant miR binding sites within coding regions, particularly those which may elicit splice-isoform specific gene suppression. This data resource may also guide future interrogations of intriguing Ago2 bindings sites within intronic regions, long non-coding RNAs (lncRNAs) and perhaps even circular RNAs (circRNAs) (46), as the functional relevance of these sites remains largely unknown. Although our luciferase data mostly point to gene suppression mechanisms for the tested miR binding sites, these experiments need to be followed-up in more biologically-relevant contexts, keeping in mind that some interactions may function as miR ‘sponges’ in competing endogenous RNA (ceRNA) expression networks (47).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a recent study in endothelial cells showed that circRNAs are regulated in response to hypoxia and have a biological function as proven by in vitro experiments [11]. Nonetheless, no rigorous reports have been published on circRNAs in murine or human heart cell types.…”
Section: Introductionmentioning
confidence: 99%
“…However, as of today, only one study has been published on the role of circRNAs in vascular cells, with particular attention to regulation by hypoxia in ECs (84). This calls for a more detailed analysis of their role in vascular development and disease.…”
Section: Long-non-coding Rnasmentioning
confidence: 99%